Intramuscular Perfusion Response in Delayed Onset Muscle Soreness (DOMS): A Quantitative Analysis with Contrast-Enhanced Ultrasound (CEUS) - Kellermann, Marion; Heiss, Rafael; Swoboda, Bernd; Gelse, Kolja; Freiwald, Jürgen; Grim, Casper; Nagel, Armin; Uder, Michael; Wildner, Dane; Hotfiel, Thilo (International Journal of Sports Medicine, 2017)
The purpose of this study was to analyse intramuscular perfusion response in ultrastructural muscle lesions, by applying contrast-enhanced ultrasound (CEUS) to a delayed onset muscle soreness (DOMS) model. Results of this analysis were compared to high-resolution 3 Tesla MRI T2-weighted sequences. 14 healthy participants were recruited. Average perfusion parameters, represented as Peak enhancement (contrast agent inflow) and wash-in area under curve (WiAUC) of the gastrocnemius (GM) and soleus muscle (SM) were assessed before (baseline) and 60 h after inducing DOMS by eccentric exercise. Additionally, conventional ultrasound, high-resolution 3T MRI, creatine kinase level, range of motion (ROM) of the ankle joint, calf circumference and muscle soreness data were collected. Perfusion quantification revealed a statistically significant increase of intramuscular perfusion, corresponding to an increase in peak enhancement of 129.6% (p=0.0031) and in WiAUC of 115.2% (p=0.0107) in the gastrocnemius muscle at post-intervention. At follow-up, the MRI investigations showed intramuscular oedema for GM in all participants corresponding to a significant rise in T2 signal intensity (p=0.001) and in T2 time value (p=0.005). CEUS seems to be able to detect intramuscular perfusion changes and therefore may contribute to gaining deeper insight into the histopathology, inflammatory reactions and regeneration processes of ultrastructural muscle lesions.
Keywords: muscle injury; CEUS; DOMS; ultrasound; MRI; eccentric exercise